OPTIMASI PRODUKSI PAVING STONE DENGAN MENGGUNAKAN METODE LINIER PROGRAMMING DI PT. XXX - Jainudin, Mukhammad; Nuriyanto (Journal Knowledge Industrial Engineering (JKIE), 2019)
Xxx is one of the companies engaged in construction that produces paving stones. The obstacle experienced by this company is that demand is sometimes soaring and sometimes soaring is caused by a lack of careful planning and maximum profits derived by the company. Therefore, companies need a certain basic calculation to optimize the amount of profit. Optimization is needed to analyze the making of paving and optimize profits by using the Linear Programming method. The purpose of this study is to determine the results of the analysis of paving production and determine the optimal profit. Retrieval of data obtained from direct observation or observation at PT. XXX. The data needed in this study are: product data, raw material purchase price data, sales data and production boundary data. In solving this problem the researchers used the Linear programming method and Smoothing forecasting methods obtained by Z_max as follows: Z_max = 540X_1 + 556X_2 + 707X_3 With the limit function: 327,27X1 318.18X2 With the requirements X_1 X_2 X_3 â‰¥ 0 So the analysis is obtained is the most optimal product sold per month are: DC 06: 106,732 M ^ 2, DC 08: 339,402 M ^ 2, TC 06: 13.109 M ^ 2 The conclusion obtained from the results of this study is that the optimal profit obtained is Rp. 75,460